Eastern Balkan roots of the pectoral from the Tovsta Mohyla - Бабенко, Леонид (Дриновський збірник, 2020)
The golden pectoral, which was found by B.M. Mozolevsky in 1971 in the Tovsta Mohyla, became widely known. However in the Scythian sphere the ornamentals of such shape didn’t have a deep tradition and actually were not spread. Many ideas that were used by a toureut when making a masterpiece, were borrowed by him from other cultural environment. The marked impact on a toureut’s conception could havebeen made by the ideas that were picked up by him from the culture of the Eastern Balkan people – Thrace and Macedonia.Many researches deem that a heavy impact on a pectoral’s conception could have been caused by breastplates from Thrace and Macedonia. They are brought together by the common shape likeness, size, composition structure as concentric visual friezes, and also by ornamentation of the middle zone with rambling floral spears. The pectoral connection with the Balkan region is reflected even more visibly by the identity of such floral ornament elements as twirled in curl spears, palmettes and acanthus leaves which form the composition of the middle frieze of the pectorals and diadems from Vergina and Stavroupoli.The idea of recreating a picture of the universe which is implemented in the pectoral composition by bas-relief figures, could have been picked up by a toureut from Homer’s description of the shield of Achilles. In this case the connecting link between the original intention of the shield of «Achilles» pectoral and breastplates from Thrace and Macedonia could be pelta shield. This kind of Thracian armor was well known by the toureuts and was implemented by them in series of work. Also very noteworthy is the recently suggested representation of scenes with anthropomorphous characters of the pectoral upper frieze, which can be related to the legend of the Macedonia dynasty origin.These and other observations give evidence of doubtless influence of Thrace and Macedonia peoples culture on pectoral master.